Stability region of 3-point block backward differentiation formula - Mahayadin, Mahfuzah; Othman, Khairil Iskandar; Ibrahim, Zarina Bibi (AIP Publishing LLC, 2013)
In this paper, we focus on the stability region of the variable step size of 3-point block backward differentiation formula (VSBBDF) method. The graphs are plotted using MAPLE software. To show the performance of the method, the accuracy is presented in the numerical results to solve first order stiff ordinary differential equations (ODEs).